Design Study of Small Modified CANDLE based Long Life Gas Cooled Fast Reactors. (December 2017) - Su'ud, Zaki; Miftasani, Fitria; Ilham,; Sarah, A.; Ariani, Menik; Sekimoto, H.; Waris, A.; Sidik, P
Abstract: Small size modified CANDLE burn-up based Long Life Gas Cooled Fast Reactors have been investigated. In this study gas cooled fast reactor system are combined with modified CANDLE burn-up scheme to create long life fast reactors with natural circulation as fuel cycle input. Such system can utilize natural uranium resources efficiently without the necessity of fuel enrichment plant or fuel reprocessing plant. The investigated power level is in the range of 200-400 MWt. For small reactors, modified CANDLE burn-up design has difficulty in term of criticality aspect. Therefore some important steps are adopted to overcome this problem. First, combined axial-radial shuffling is adopted. Then, high fuel volume fraction of about 65% is adopted. The optimization processes is then conducted which includes adjustment of fuel region movement scheme, volume fraction adjustment, core dimension, etc. Due to the limitation of thermal hydraulic aspects, the maximum average power density of the proposed design is selected of about 75 W/cc. All proposed reactor design are operated for 10 years without refueling or fuel shuffling with just need natural uranium as fuel cycle input in every beginning of 10 years of cycle. With such conditions small sized cores from 200MWt to 400 MWt were investigated and optimized. The average discharge burn-up is about 20% HM. As an example, the dimension of 200 MWt case is 90 cm in radius and 180 cm height for the active core part. The reflector is 70 cm with. The burn-up level is about 20% HM.